In Vitro biological assessment of plasma electrolytic oxidation-treated magnesium alloys containing multiple nutrient elements - Renuga Devi K; Sreekanth Dondapati (Results in Engineering)
Magnesium-based alloys are increasingly recognized for biodegradable orthopaedic implants due to their favourable mechanical properties and biodegradability. This study aims to assess the invitro biological behaviour of two magnesium-based alloys: a high entropy alloy (HEA) Mg82(CaMnZn)15Sn2(AgCeSr)1 and a micro alloy (MA) Mg-0.1Ag-0.15Ca-0.2Ce-0.1Mn-0.1Sn-0.2Sr-0.5 Zn. The main objective is to study the influence of multiple alloying elements including nutrient elements and further surface modification via Plasma Electrolytic Oxidation (PEO) on their biodegradation behavior, cytocompatibility, osteogenic potential, and antibacterial activity. Biodegradation studies revealed that the PEO treated micro alloy exhibited the lowest corrosion rate and alkalization, demonstrating the effectiveness of the PEO coating in enhancing corrosion resistance. Cytocompatibility, assessed through cell viability assays, showed excellent biocompatibility for both MA and PEO treated MA, outperforming HEA. Osteogenic potential was evaluated using ALP activity and ARS staining, where PEO treated MA exhibited the highest osteogenic activity, attributed to its bioactive alloying elements and the biofunctional PEO coating. Antibacterial tests against Staphylococcus aureus and Escherichia coli revealed that PEO treated MA exhibited the highest bacterial inhibition of ∼70 %, followed by MA, due to controlled ion release and the bioactive surface. In conclusion, the micro alloy with PEO coating demonstrated superior performance across biodegradation, cytocompatibility, osteogenic potential, and antibacterial activity, highlighting its promise for application in biodegradable orthopedic implants.